Pengaruh Kepemimpinan Transformasional, Komitmen Organisasi dan Burnout Terhadap Kinerja Karyawan: (Studi pada Karyawan Non-Manajerial Hotel Grand Aston Yogyakarta) - Jonathan Christ; Tri Mardiana; Hery Sutanto (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
This study aims to determine (1) The effect of transformational leadership, organizational commitment, and partial burnout on the performance of non-managerial employees at the Grand Aston Hotel Yogyakarta, (2) The effect of transformational leadership, organizational commitment and burnout together on the performance of non-managerial employees Grand Aston Yogyakarta Hotel, (3) Which variable has the most dominant influence on the performance of non-managerial employees at Grand Aston Yogyakarta Hotel. Sampling used in this study is saturated sampling (census), in which all members of the population are sampled. The number of non-managerial employees at Grand Aston Yogyakarta Hotel is 116 people. This study uses a survey method that is research conducted using a questionnaire as a research tool. Data collection by interview and questionnaire was compiled with a Likert Scale and then calculated using the SPSS method. The results of this study are (1) Transformational leadership, organizational commitment, and burnout have a partial effect on the performance of non-managerial employees at the Grand Aston Yogyakarta Hotel; (2) Transformational leadership, organizational commitment and burnout have an effect on together with the performance of non-managerial employees of the Grand Aston Yogyakarta Hotel; (3) Transformational leadership has the most dominant influence on the performance of non-managerial employees at the Grand Aston Yogyakarta Hotel.